Air Assisted Dispersive Liquid–Liquid Microextraction (AA-DLLME) Using Hydrophilic–Hydrophobic Deep Eutectic Solvents for the Isolation of Monosaccharides and Amino Acids from Kelp. (22nd January 2020) - Li, Guizhen; Row, Kyung Ho
Abstract: Air assisted dispersive liquid–liquid microextraction (AA-DLLME) using hydrophilic–hydrophobic deep eutectic solvents (DES) was developed for the simultaneous isolation of monosaccharides and amino acids with wide ranges of polarities from kelp using high performance liquid chromatography (HPLC). A response surface methodology (RSM) on a Box–Behnken design (BBD) model was employed to identify the optimal extraction parameters. Air assisted dispersive liquid-phase microextraction performed using the optimum deep eutectic solvent system, five push–pull cycles, a ratio of solid to liquid equal to 3 mg·mL −1, 10% ( w/v ) NaCl, and a centrifugation time of 6 min provided the best analytical performance. The optimal extracted concentrations of d -(+)-galactose, l -(-)-fucose, dl -tyrosine, and dl -valine in kelp were 16.7 ± 0.2, 8.6 ± 0.2, 2.6 ± 0.1, and 1.6 ± 0.1 mg·g −1, respectively. The method recoveries for d -(+)-galactose, l -(-)-fucose, dl -tyrosine, and dl -tyrosine were from 87 to 102%, 84 to 103%, 87 to 104%, and 85 to 103%. The relative standard deviations (RSDs) ( n  = 4) for the intra-day and inter-day determinations were <6.17%.